2016
DOI: 10.1002/adfm.201600680
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed and Low‐Energy Nitride Memristors

Abstract: High‐performance memristors based on AlN films have been demonstrated, which exhibit ultrafast ON/OFF switching times (≈85 ps for microdevices with waveguide) and relatively low switching current (≈15 μA for 50 nm devices). Physical characterizations are carried out to understand the device switching mechanism, and rationalize speed and energy performance. The formation of an Al‐rich conduction channel through the AlN layer is revealed. The motion of positively charged nitrogen vacancies is likely responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
202
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(205 citation statements)
references
References 45 publications
2
202
0
1
Order By: Relevance
“…19 The second challenge is to design the experiment in a way that the generated signal is preserved until it reaches the ReRAM device. Therefore, every component in the setup has to be chosen carefully and requires a high bandwidth.…”
Section: Experimental: Approaching the Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The second challenge is to design the experiment in a way that the generated signal is preserved until it reaches the ReRAM device. Therefore, every component in the setup has to be chosen carefully and requires a high bandwidth.…”
Section: Experimental: Approaching the Limitmentioning
confidence: 99%
“…[15][16][17] Switching below 100 ps was shown for a Pt/SiO 2 -based device 18 and the record switching speed of <85 ps was achieved for a nitride-based resistive switch. 19 In all of these studies, however, it was concluded that the switching speed was still limited by the measurement setup.…”
Section: Introductionmentioning
confidence: 99%
“…A class of memristors used in memory applications is also often called resistive random access memory (RRAM) 4,5 . Fundamental device studies have shown that the device can be scaled to sub-10 nm feature sizes 6 and retain memory states for years 7 , while offering desirable device properties such as subnanosecond switching speed 8,9 , long write-erase endurance 10 and low programming energy (for example, nanoamperes 11 ). It should be noted that while many of the above favourable properties have been realized repeatedly, a single material system that combines them all simultaneously remains an open challenge.…”
mentioning
confidence: 99%
“…However, with the continuous downscaling of the memory cell down to 10 x 10 nm 2 and below, the persistence of this phenomena raises intriguing questions on the conductive filaments (CFs) and its dimensions. Particularly, the cell functionality demonstrated at relatively high switching current (> 100 µA) implies a high current density (> 10 6 A/cm 2 ) inside a CF supposedly confined in few hundreds on nm 3 . We previously demonstrated a methodology for the direct observation of CFs in integrated devices namely scalpel SPM, which overcomes most of the characterization challenges imposed by the device structure and the small CF lateral dimensions.…”
mentioning
confidence: 99%
“…[3][4][5][6] The mechanism of the resistive switching in these devices has been identified as a clustering of localized valence changes leading to the formation of a conductive filament (CF) inside the dielectric. [7][8][9] The resistance of the CF is related to the ionic migration and nanoscale chemical reactions driven by the electric field.…”
mentioning
confidence: 99%